Urgensi pemilihan pesantren sebagai tempat domisili mahasiswa - Khoiri, Muhammad Imamul (Maliki Interdisciplinary Journal, 2023)
Pesantren is an Islamic educational institution that provides an environment to support students (santri) in developing their spiritual, academic, and social aspects. Students greatly benefit from the environment within pesantren that aids in their personal, spiritual, and social development. Therefore, the choice of pesantren as a place of residence for students holds an urgency that can yield positive impacts on the self, spiritual, academic, and social growth of students.